Emerging insights into the immunological aspects of keloids. Issue 12 (21st September 2021) - Yu, Yangyiyi; Wu, Haijing; Zhang, Qing; Ogawa, Rei; Fu, Siqi
Abstract: A special kind of scar, keloid, sometimes grows huge, disturbing patients in different ways. We discussed the pathogenesis of keloids and found researches about fibroblasts and collagen disorders, with little emphasis on immunity. Coupled with few effective treatments in keloid at present, we have focused on the immunological mechanisms of keloids with an aim to unravel some new therapeutic approaches in the future. In this review, the immunological processes are separately illustrated by the classification of different immune cells. In addition, we also discuss possible reasons for the repeated recurrence of keloids, the phenomenon of cell talks, and inflammation‐related signal pathways involved in the pathogenesis of keloids.